Sentire il groove: aspetti percettivi e partecipativi - Bottin, Guglielmo (Scenari, 2024)
The study of groove is part of a general re-evaluation of rhythm that took place towards the end of the 20th century. The phenomenon of groove is commonly associated with pleasurable involvement and synchronization with musical rhythm, inducing responses that are expressed in body movements and psychological entrainment. In syntactic/structural theories, groove is believed to emerge from a combination of cyclically repeated rhythmic lines, while in processual/performative interpretations, it is considered in terms of a musician’s embodied rhythmic sensibility or as the result of interplay in ensemble performance. Whether groove is considered in terms of ‘text’ or performance, scholars often refer to a unified set of parts, similar to the psychological concept of Gestalt. This essay aims to place groove among the pillars of a more general aesthetic theory of popular music, evaluating both the expressive-performative and deliberately machinic aspects of programmed and electronic popular music. Thus, groove is seen as an aesthetic trait aimed at encouraging direct and immediate participation, which occurs through active and embodied experiences and not through formal intellectual contemplation.